Re-modelling Muslim-friendly tourism value chain ecosystem: the case study of West Sumatera, Indonesia - Anang Sutono; Sumaryadi; Wisnu Rahtomo; Faisal Fahdian Puksi; Odang Permana (Cogent Social Sciences)
The development of Muslim-friendly tourism destinations is an effort to differentiate products and the tourism market amidst the aggressive growth of global tourism. This is the background for this research, which aims to examine the implementation of Muslim-friendly tourism in West Sumatra and strive to form a Muslim-friendly tourism value chain model from research findings. This research relies on collecting primary data from interviews with nine informants collected using snowball sampling and secondary data support from relevant literature and regulatory products. Using a qualitative descriptive method and SWOT analysis to map actual conditions in the field, the data findings and the analysis process state that the tourism value chain has been formed and is moving in West Sumatra. The value chain is formed from the support of destination attributes, regulations and digital technology adaptation. However, there needs to be significant changes in institutional aspects, diversification of activities/events and community empowerment.